(untitled) (Scientific journal of the Fergana State University, 2025)
The essence of philosophical and ethical views was analyzed with the help of Sufi life and mystical views. The development of Sufism is based on an irrational approach to the philosophical understanding of Sufi ethics. To understand ethical views, an example of scientific approaches to Sufism and Sufis was considered.